2019
DOI: 10.2478/hukin-2019-0055
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Grip Width on Training Volume During the Bench Press with Different Movement Tempos

Abstract: The aim of the study was to determine the effect of the wide-grip bench press (WGBP) and the close-grip bench press (CGBP) on the number of performed repetitions (REPs) and time under tension (TUT) using a variable tempo of movement. Twenty (20) women experienced in resistance training were enrolled in the study (1RM-CGBP = 55.2 ± 9.5 kg; 1RM-WGBP = 52.7 ± 8.5 kg). Participants performed 5 sets of the BP with a maximal number of REPs at 70%1RM. Different tempos of movement, i.e., slow (6/0/X/0) and fast (2/0/X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 41 publications
2
54
2
Order By: Relevance
“…Prior to the 1RM trials, the participants were re-evaluated for their technical execution of the exercise with and without the SS. During the familiarization session the SS, size was adopted for each participant on the basis of bodyweight and consultation with a resistance training coach (medium, large, and extra-large size range, whereas each size provides the same tension), and the bench press grip width adopted for all sessions was 150% bi-acromial distance of each subject [ 15 ]. The participants arrived in the laboratory at the same time of the day as the upcoming experimental sessions and cycled on an ergometer for 5 min, followed by a general upper body warm-up.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the 1RM trials, the participants were re-evaluated for their technical execution of the exercise with and without the SS. During the familiarization session the SS, size was adopted for each participant on the basis of bodyweight and consultation with a resistance training coach (medium, large, and extra-large size range, whereas each size provides the same tension), and the bench press grip width adopted for all sessions was 150% bi-acromial distance of each subject [ 15 ]. The participants arrived in the laboratory at the same time of the day as the upcoming experimental sessions and cycled on an ergometer for 5 min, followed by a general upper body warm-up.…”
Section: Methodsmentioning
confidence: 99%
“…While there is extensive literature on the bench press movement [ 2 , 5 , 9 , 14 , 15 ], far less attention has been given to the influence of performance enhancing equipment on maximum strength and muscle activity. Currently, powerlifters at the highest level are implementing specialized gear (i.e., squat suits, bench press shirts, deadlift suits, and knee wraps) to enhance performance [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, several studies have confirmed the effect of the movement tempo on the number of repetitions performed, time under tension and exercise volume (Sakamoto & Sinclair, 2006;Wilk et al, 2018a;2018b;2018c;2019a), but the present study is the first one which analysed both the movement tempo and the width grip. Results of the present study are consistent with previous findings of Wilk et al (2019), who showed increase level of power output and bar velocity during the BP with fast movement tempo compared to slower one.…”
Section: Discussionmentioning
confidence: 65%
“…However, athletes also often use the wide-grip bench press (WGBP) and the close-grip bench press (CGBP). The WGBP is described as a bench press with a grip width of 200% or more of the biacromial distance (BAD), while the CGBP is defined as a grip width of 95% BAD (Wagner et al 1992; Barnett et al, 1995;Lockie et al, 2017a;2017b;Wilk et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies documented at least minor improvements in jumping test results following PAP exercise protocols. In addition, there is a lack of studies describing the PAP phenomenon using the internal structure of the movement (Krol andGolas 2017, Golas 2018), different time of tension (Wilk et al 2019a, Wilk et al 2019b and training using blood flow restriction , which should constitute future research directions. The studies presented in this review have also demonstrated the effectiveness of PAP in warm-up protocols on explosive strength, agility and jumping performance.…”
Section: Resultsmentioning
confidence: 99%